Accelerating ozone layer protection in developing countries. - Munasinghe, Mohan (1992)
Argues that the seriousness of the ozone problem implies that the benefits of ozone layer protection are extremely high, and that the global imperative should be to maximise benefits rather than minimise costs of control. Examines the Montreal Protocol as it currently stands in relation to the criterion of rapid, cost-effective phase out.